A promising potential candidate for vascular replacement materials with anti-inflammatory action, good hemocompatibility and endotheliocyte-cytocompatibility: phytic acid-fixed amniotic membrane. (23rd September 2021) - Cheng, Can; Peng, Xu; Qi, Hao; Wang, Xu; Yu, Xiaoshuang; Wang, Yuhang; Yu, Xixun
Abstract: Due to its excellent biocompatibility and anti-inflammatory activity, amniotic membrane (AM) has attracted much attention from scholars. However, its clinical application in vascular reconstruction was limited for poor processability, rapid biodegradation, and insufficient hemocompatibility. A naturally extracted substance with good cytocompatibility, phytic acid (PA), which can quickly form strong and stable hydrogen bonds on the tissue surface, was used to crosslink decellularized AM (DAM) to prepare a novel vascular replacement material. The results showed that PA-fixed AM had excellent mechanical strength and resistance to enzymatic degradation as well as appropriate surface hydrophilicity. Among all samples, 2% PA-fixed specimen showed excellent human umbilical vein endothelial cells (HUVECs)-cytocompatibility and hemocompatibility. It could also stimulate the secretion of vascular endothelial growth factor and endothelin-1 from seeded HUVECs, indicating that PA might promote neovascularization after implantation of PA-fixed specimens. Also, 2% PA-fixed specimen could inhibit the secretion of tumor necrosis factor- α from co-cultured macrophages, thus might reduce the inflammatory response after sample implantation. Finally, the results of ex vivo blood test and in vivo experiments confirmed our deduction that PA might promote neovascularization after implantation. All the results indicated that prepared PA-fixed DAM could be considered as a promising small-diameter vascular replacement material.